POLA GERAKAN SOSIAL: RESISTENSI MASYARAKAT SAMIN DI ERA GLOBALISASI - Cahya Pratama (Jurnal Ilmiah Dinamika Sosial, 2021)
Today the progress of human civilization is progressing rapidly. Social change is no longer a foreign thing in the era of globalization. One of the indigenous peoples, namely the Samin community, has strong characteristics and the establishment to maintain its existence in social life. The Samin community has always carried out social movements against government policies that have damaged the lives of the Samin people. This article aims to review the Samin community in the era of globalization where all aspects of life are progressing quite rapidly. The era of globalization is very vulnerable to values, culture and norms that easily enter the order of people's lives. This study uses a literature study research method. Sources of research come from sources of journals and books that are in accordance with the discussion. The results of this study indicate that the Samin community uses the Gethok Tular communication pattern to convey information about the Samin community's unrest to other communities. Keywords: Social Movement, Society, Samin, Globalization